PRELIMINARY STUDIES ON HYDROMETALLURGICAL TIN RECOVERY FROM WASTE OF TIN STRIPPING OF COPPER WIRES (Metallurgy and Foundry Engineering, 2017)
This paper presents the results of tin leaching and electrowinning from SnO2 waste originating from the industrial process of tin stripping of copper wires. The sludge was leached by acids (sulfuric, hydrochloric, tartaric, oxalic) and sodium hydroxide at various temperatures (40–80°C). The highest efficiency of tin leaching (12–18%) was obtained in an oxalic solution, while the lowest effectiveness (0.2–0.5%) was found for sulfuric acid. Tin leaching was accompanied by a transfer of copper residues to the solution. The electrowinning stage was realized under potentiostatic and galvanostatic conditions using oxalate solutions. Cyclic voltammetry was applied to select the potentials for the selective deposition of metals.